Volume 3: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-53401
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of Flow and Heat Transfer in a Channel Roughened by Square or Semicircle Ribs

Abstract: The internal cooling passage of a gas turbine blade can be modeled as a ribbed channel. So far, most studies have considered square ribs. However, the ribs can be rounded due to improper manufacturing or wear during the operation. Round ribs have also been tested expecting that they may enhance the thermal and aerodynamic performance. Hence, we have studied two different rib geometries in this study, i.e. square and semicircle ribs. Large eddy simulations (LES) of turbulent flow in a ribbed channel with a dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…Among these, one may cite: [1,2,26,27,34,39]. Nevertheless, in most of these investigations, the main interest was focused on reproduction and prediction of the Eulerian statistics (average) and of the resolved turbulent field, without a real topology analysis.…”
Section: Introductionmentioning
confidence: 98%
“…Among these, one may cite: [1,2,26,27,34,39]. Nevertheless, in most of these investigations, the main interest was focused on reproduction and prediction of the Eulerian statistics (average) and of the resolved turbulent field, without a real topology analysis.…”
Section: Introductionmentioning
confidence: 98%
“…In common, ribs are adopted to form artificial roughness, which provide heat transfer enhancement by generating vortices [23]. Therefore, the coupling ribs with HST is likely to give combined effect of common swirl and vortex in the flow which should give rise to stronger turbulent intensity and thus better fluid mixing as compared to those given by HST or ribs alone.…”
Section: Introductionmentioning
confidence: 99%
“…The ribs are reported to enhance heat transfer by generating vortices [2], but they also create a separation bubble behind the rib, where heat transfer does not actively take place. To remove this region, Marumo et al [3] tried to displace the rib by a small distance from the wall and showed an improved heat transfer rate depending on the clearance between the rib and the wall, whose optimum value was suggested as c/e = 0.5, where c is the clearance and e is the rib height as schematically shown in Fig.…”
Section: Introductionmentioning
confidence: 99%